PENGARUH LITERASI KEUANGAN DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUTUSAN PENGGUNAAN UANG DIGITAL - Sibuea, Christina Aprilia; Simorangkir, Helmina Handayani; Nababan, Cintia; Nadapdap, Tomi Irianto; Siallagan, Hamonangan; Sipayung, Rizky (Politeknik Negeri Ambon, 2023)
A quantitative study was conducted to better understand the limitations of perceptions of ease of use and perceived utility related to the use of electronic currency (ShopeePay). The study population was residents of the public. Non-probability sampling and purposive sampling techniques,30 samples were used in this study. The collection is done using Google Forms for submissions from users, and SPSS is used for other data. The results showed that financial literacy was 0.732 with a significance of 0.402>0.05 and the ease of use measured was 0.852 with a significance of 0.640>0.05.